INTELLECTUAL PROPERTY ENFORCEMENT TO SAFEGUARDING IT ENVIRONMENT - Mohammad Salim Abdulrahman; Mazin S. Al-Hakeem (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The world has started to appreciate more and more the value of information and its impact on humanity and sustainable developments. However, due to the increase in cybercrimes, information technology needs to be secured using certain policies and laws. In Iraq, as one of the developing countries, information technology field has evolved but the readiness to secure information technology is believed to be at the infancy. This paper introduces the potential role of intellectual property in safeguarding information technology from infringed and theft threats. It also suggests some recommendations as a basis for developing intellectual property law and policies to protect the rights of information technologies in Iraq.